0 рейтинг
16 видели

А) (1,1x - 0,21c) + (2,2x - 4b) - (3,3x - 4b) = B) (2,31x - 2,37c) - (2,47x - 0,33c) - (2,4c - 0,16x) = C) - (0,1a + 1,1b) - (0,7b - 1,05a) - (1,1b + 0,95a) = D) (a + c) • ( - 2,1) - (5,3a - 2,1c) = E) 2,06 • (x - c) + (1,03x - 2,51c) • (- 2) =

от (12 баллов) в разделе Математика | 16 видели

2 Ответов и Решений

0 рейтинг

A)1.1x-0.21c+2.2x-4b-3.3x+4b=(1.1x+2.2x-3.3x)+(-4b+4b)-0.21c=0+0-0.21c=-0.21c   B)(2.31x-2.47x+0.16x)+(-2.37c+0.33c+2.4c)=0+0.4c=0.4c   C)(-0.1a +1.05a-0.95a)+(-1.1b-0.7b-1.1b)=0-2.9b   D)-2.1a-2.1c-5.3a+2.1c=-7.4a              E)2.06x-2.06c-2.06x+5.02c=2.96c

от (53 баллов)
0 рейтинг

А=1,1x - 0,21c+ 2,2x - 4b- 3,3x + 4b=-0.21

от (18 баллов)
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей